Islet NADPH oxidase activity modulates β-cell mass and endocrine function in rats with fructose-induced oxidative stress - Román, Carolina Lisi (2014)
Background: Islet NADPH oxidase activity is modulated by glucose and other insulin secretagogues and it might be part of the regulatory mechanism of insulin secretion. We studied its modulatory role of islet NADPH oxidase upon β-cell function in rats with fructose-induced oxidative stress. Methods: Normal rats were fed for 3 weeks with a standard diet, a fructose-rich diet or both diets plus apocynin. We measured plasma glucose, insulin, triacylglycerol and lipid peroxidation levels and the homeostasis model assessment-insulin resistance (HOMA-IR) and HOMA-β indexes, and performed an oral glucose tolerance test. β-cell volume density and the number of islets per mm2 were determined by immunomorphometric analysis of the pancreas. Insulin secretion, glucose metabolism, glucokinase and NADPH oxidase activities were studied in islets isolated from each experimental group. Results: Fructose-fed rats had increased plasma triacylglycerol, insulin and lipid peroxidation levels associated with an insulin resistance state; the reactive higher secretion was unable to cope with the increased demand of insulin, leading to an impaired glucose tolerance. They also have a lower number of islets per area unit with a decreased β-cell volume density. All these alterations were prevented by blocking NADPH oxidase activity with apocynin. Conclusion: Fructose-induced changes are partly mediated by modulation of NADPH oxidase activity. General significance: The metabolic dysfunctions and enhanced oxidative stress measured in fructose-fed rats resemble those recorded in human prediabetes; thus, successful strategies employed in this model could be later used to prevent the progression of this state towards type 2 diabetes in human beings.